Властивості середньозернистого твердого сплаву ВК3, спеченого за температури існування рідкої фази - Юрчук, М.О. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2009)
The paper describes the peculiarities of the formation of the medium-grained low-cobalt
WC-3Co cemented carbide at sintering temperatures of 1300, 1350, 1400, 1450, 1470, 1500, 1520,
1550 and 1750 °C.